Adição de agentes antioxidantes na solução de vitrificação do tecido ovariano ovino: Uma perspectiva para refinar e aperfeiçoar o protocolo - Silva, Luciana Mascena (2017)
Vitrification of ovarian tissue prior to gonadotoxic treatments is an alternative to preserve follicular reserve, with the aim of subsequent reimplantation and consequently, restoration of female fertility. However, the vitrification process causes some damage which should be minimize. Thus, Therefore, the objective of this study was to verify the catalase and alpha lipoic acid in different concentrations to reduce generation of reactive oxygen species (ROS), aiming to obtain less damage on follicular morphology and development, stromal cell density, alterations in the DNA, as well as mitochondrial activity of ovine preantral follicles. To achieved this objective, sheep ovarian fragments were distributed in 9 treatments: (1) fresh or control; (2) incubated for 24h (INC); (3) vitrified without antioxidants (SAA) or in the presence of catalase (CAT) at concentrations of (4) 10 - CAT10; (5) 20 - CAT20 or (6) 40 - CAT40 IU / ml or in the presence of ALA at concentrations of (7) 25 - ALA25; (8) 50-ALA50 or (9) 100 μM / ml (ALA100). After vitrification, all the fragments were warmed followed by incubation for 24 hours, finally, morphology and follicular development as well as ROS levels in the incubation medium were evaluated. Afterwards, the fragments of control, INC, SAA, CAT40 and ALA100 groups were analyzed for stromal cell density, DNA damage (TUNEL test and H2AX phosphorylation), ROS levels and mitochondrial function. The data were submitted to the statistical package SAS, and according to the behavior of the data and the differences were considered significant different when P <0.05. Unlike the other treatments, the percentage of morphologically normal follicles in the ALA groups with all the concentrations did not differ from the fresh tissue. Moreover, the percentage of developing follicles was higher in ALA100 than those found in the CAT40, ALA25 and ALA50 groups. However, whilst the treatment ALA100 maintained mitochondrial activity, it was not sufficient to control intracellular ROS production. In contrast, the treatments CAT10 and CAT20 significantly affected the ROS levels, stromal cell density as well as DNA damage revealed by γH2AX (CAT40). Additionally, the ovarian morphology was well preserved ALA100. It also promoted follicular development and caused less damage to the DNA of the preantral follicles. Despite the satisfactory results of the present study, it is fundamental to carry out new studies to define the ideal ALA concentration, in order to improve all the parameters evaluated.